Tinjauan Kemungkinan Sebaran Unsur Tanah Jarang (REE) di Lingkungan Panas Bumi - Herman, Danny Zulkifli (Geological Agency, 2009)
http://dx.doi.org/10.17014/ijog.vol4no1.20091Geothermal areas occur mainly in an environment of volcanic/magmatic arc where magma chambers play a role as heat sources. The environment is situated within the convergent plate boundaries. A variety of igneous rocks is associated with this environment ranging from basalt (gabbro) to rhyolite (granite) but andesite is normally the most abundant igneous rock. The most obvious geothermal indications are exhibited by some surface manifestations comprising hot water seepage, fumaroles, hot spring, geyser, and hydrotermal alteration zones which are being evidences of an active hydrothermal system beneath the surface as a part of volcanism. Despite being a causal factor for alteration of country rocks, most hydrothermal fluids enable to change distribution pattern and content of rare earth elements (REE for instance Ce, Eu, La, Lu, Sm, Nd, and Y) particularly during a reaction process. This may have a connection with development of element mobility rates, whilst the characteristics of REE pattern within hydrothermal fluid would have a high variable due to dependency of their original magma source. Considering the important role of hydrothermal fluid in REE mobility development, it is inspired to review the possible relationship of active hydrothermal system and potency of REE distribution pattern in areas of geothermal manifestation. Â